Pertanggungjawaban Pidana atas Perundungan Tersistem dalam Sistem Peradilan Pidana di Indonesia - Morena asmara; Muhammad Azil Maskur (AL-SULTHANIYAH, 2026)
Systemic bullying within workplaces constitutes a criminal law issue that has not yet received adequate scholarly attention, particularly regarding the criminal liability of parties who fail to take preventive action against such conduct. This study aims to analyze the forms of criminal liability arising from systemic bullying within the Indonesian criminal justice system. The research employs a normative legal method, utilizing statutory, conceptual, and case approaches. The findings indicate that systemic bullying does not solely originate from the actions of direct perpetrators, but is also shaped by omission, weak supervision, and the failure of those holding supervisory authority to fulfill their duty of care. Within the framework of criminal law, liability for systemic bullying is closely related to the elements of causality and culpability, particularly negligence (culpa). These findings underscore that criminal liability should not be limited to the direct perpetrators, but may also extend to institutional leaders who allow such bullying to occur. This study contributes to the development of Indonesian criminal law, particularly in strengthening the normative foundation of criminal liability for systemic bullying within educational institutions and workplaces.